Age Differences in Perceived Psychological Stress Among Moroccan Professional Football Players - Hicham, Brir; Ridouane, Haimer; Aicha, Ziani (International Journal of Education, Culture, and Society, 2025)
This study explores the relationship between age and perceived psychological stress among Moroccan professional football players. Using a descriptive-analytical approach, data were collected from 250 players in the first and second divisions of the Moroccan Professional League, divided into four age groups: under 20, 21–25, 26–30, and over 31. The results revealed a significant inverse relationship between age and stress levels. Players under 20 experienced the highest stress, with 46.43% reporting high-stress levels, while only 13.16% of players over 31 reported the same. Mid-career players (26–30 years) showed more balanced stress levels, benefiting from both experience and physical peak performance. Statistical analysis using the Chi-square test confirmed this trend (χ² = 19.1296, p =<0.01), indicating a significant link between age and perceived stress. These findings suggest that younger players struggle more with stress due to limited experience and coping skills, while older players benefit from greater psychological resilience. Based on this, we recommend age-specific psychological interventions to enhance stress management strategies for football players at different career stages.